Relationships between biotic and abiotic range characteristics and productivity of reindeer husbandry in Sweden - Henrik Lundqvist; Lennart Norell; Öje Danell (Rangifer, 2009)
Reindeer husbandry is a form of pastoralism where vast areas are used as forage ranges throughout the year. The productivity of the reindeer industry in Sweden is affected by a multitude of factors on different geographical and temporal scales. Our aim was to find combinations of factors characterizing the environmental conditions for reindeer husbandry in the 51 herding districts in Sweden, which correlate strongly with variations in productivity both between herding districts in general and between years within districts. Productivities were described by estimated herd growth rates and carcass condition of slaughtered females and calves. These dependent variables were related to the environmental independent variables using linear regression models and structural equation modelling. The independent variables were either considered as stable (e.g. topography, vegetation and infrastructure) or temporally changing (e.g. season lengths, weather events, disturbances and animal slaughter strategies). The most relevant independent variables were included in a cluster analysis to suggest a grouping of herding districts based on similarities in environmental conditions. Considerably larger variation in productivity was found between herding districts than between years. Different variables were found to be important for between-district and within-district variations, respectively. Season lengths and animal densities were found significant at both levels of variation. Other variables found to be relevant were ruggedness, snow condition, harassing insect activity, supplementary feeding, calf slaughter ratio and previousyear animal condition. Snow precipitation, ice-crust formation and forage quality were presumed to be relevant for reindeer productivity, but were not found to have a large impact on productivity. These factors, however, may have been counteracted by husbandry measures, statistically incorporated in animal density variables, or by being strongly correlated with other, more significant variables. Several ...